The Effect Of Using K-W-L Teaching Method On Reading Comprehension In Descriptive Text - Fatkhur Rokhim; Anita Fatimatul Laeli; Fitrotul Mufaridah (SS&H: Studies in Social Sciences and Humanities, 2024)
For L2 teachers to enhance their students' L2 reading abilities, they must take into account an appropriate teaching approach that can impact reading accomplishment in a second language (L2) and solve students’ problem in learning foreign language. In learning reading skill, several Indonesian students have their own difficulties such as challenging vocabulary, understanding sentences, accurately reading words or sentences, and so forth. Those problems make Indonesian language learner feel frustrated and give up in learning language, on top of that, the conventional teaching method also can’t boost their interest to learn English language. However, A lot of studies had conducted to investigate the various of teaching method particularly K-W-L teaching method that has an impact on reading comprehension. Further, K-W-L method has a lot of advantage when it is implemented in learning language it’s like encourage student reading interest and reading comprehension. The current study fills this gap by investigating the effectiveness K-W-L method in improving learning achievement in terms of reading comprehension. The fundamental claim of this research is that the K-W-L method of instruction may have an effect on students' ability to understand what they read and retain information in a descriptive text. Thirty-three junior high school students completed reading exams (pre-test and post-test) using two different forms of descriptive but they were divided into two classes to find the difference in reading abilities of students who were treated using K-W-L method and students who were not. The effect of K-W-L as a teaching strategy on students' reading comprehension will be assessed by comparing the outcomes of the two assessments. According to test scores, there were disparities in EFL reading comprehension, as revealed by the statistical analysis, suggesting that this teaching strategy is important in determining the reading accomplishment of EFL students. These findings offer valuable information about how the K-W-L method may be structured and put into practice to help L2 learners improve their L2 reading proficiency and students' engagement. The paper concludes with a few recommendations for additional research in the K–W–L domains, including L2 reading and L2 teaching methods.